On intermediate-scale open-sea experiments on floating offshore structures: Feasibility and application on a spar support for offshore wind turbines. (September 2018) - Ruzzo, Carlo; Fiamma, Vincenzo; Collu, Maurizio; Failla, Giuseppe; Nava, Vincenzo; Arena, Felice
Abstract: Experimental investigation of floating structures represents the most direct way for achieving their dynamic identification and it is particularly valuable for relatively new concepts, such as floating supports for offshore wind turbines, in order to fully understand their dynamic behaviour. Traditional experimental campaigns on floating structures are carried out at small scale, in indoor laboratories, equipped with wave and wind generation facilities. This article presents the results of an open-sea experimental activity on a 1:30 scale model of the OC3-Hywind spar, in parked rotor conditions, carried out at the Natural Ocean Engineering Laboratory (NOEL) of Reggio Calabria (Italy). The aim of the experiment is two-fold. Firstly, it aims to assess the feasibility of low-cost, intermediate-scale, open-sea activities on offshore structures, which are proposed to substitute or complement the traditional indoor activities in ocean basins. Secondly, it provides useful experimental data on damping properties of spar support structures for offshore wind turbines, with respect to heave, roll and pitch degrees of freedom. It is proven that the proposed approach may overcome some limitations of traditional small-scale activities, namely high costs and small scale, and allows to enhance the fidelity of the experimental data currently available in literature for spar floating supports for offshore wind turbines. Highlights: Open-sea experiment on a 1:30 SPAR for floating offshore wind turbines was carried out. Design and realization of the experimental activity are presented in detail. Damping properties and Response Amplitude Operators are identified from experiment. A numerical model of the structure is calibrated using experimental data. The proposed approach is generalized for future application on floating structures.